Analisis Tingkat Kepuasan Pengguna Sistem Absensi Guru di SMK Negeri 17 Jakarta Menggunakan Metode End-User Computing Satisfaction - Dzaky Naufal; Goldie Gunadi (Lembaga Pengembangan Kinerja Dosen, 2025)
The development of inFormation technology has encouraged educational institutions to continuously innovate in administrative system management, including employee attendance processes. SMK Negeri 17 Jakarta has implemented a computerized digital attendance system as a replacement for the manual method. The purpose of this study is to analyze user satisfaction levels with the implemented employee attendance system using the End-User Computing Satisfaction (EUCS) method, which includes five variables: content, Accuracy, Format, ease of use, and timeliness. This research employs a descriptive quantitative method. Data collection techniques include distributing questionnaires to system users (teachers/staff), direct observation, and document analysis. Data analysis was conducted through instrument validity and reliability testing, as well as calculating the satisfaction percentage for each variable. The results show that all variables fall within the “satisfied” category, with relatively high average scores. The variable with the highest score is Timeliness at 82.4%, followed by Ease of Use at 79.8%, Content at 79.2%, Accuracy at 77.2%, and Format at 76.6%. These findings indicate that the digital attendance system has met users' needs in terms of accessibility, speed, and inFormation Accuracy. In conclusion, the system is effective in supporting employee attendance management, enhancing discipline, and strengthening administrative performance within the school environment.